Preparation method and application of carbon-coated cobalt phosphide and carbon-coated cobalt phosphide loaded carbon nitride
The carbon-coated cobalt phosphide is prepared by one-step thermal cracking method of cobalt Schiff base complex, and the morphology of the catalyst is regulated by introducing carbon nitride, which solves the complex synthesis of carbon-coated cobalt phosphide catalysts in the prior art and is costly. The problem of poor catalytic stability has achieved efficient electrocatalytic nitrite reduction and synthesis of ammonia.
Patent Information
- Application Number
- CN202411666507.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-18
AI Technical Summary
In the prior art, the synthesis method of carbon-coated cobalt phosphide catalyst is complex and costly, and in the NOxRR reaction, there are problems such as severe hydrogen evolution reaction, low selectivity for ammonia synthesis, and poor catalytic stability.
Carbon-coated cobalt phosphide was prepared by one-step thermal cracking phosphating method of cobalt Schiff base complex, and the particle size and morphology of the catalyst were regulated by introducing carbon nitride, providing electronic regulation and improving catalytic activity and stability.
The significant catalytic effect and excellent cyclic catalytic stability of synthesis of ammonia under normal temperature and pressure were achieved, and the Faraday efficiency and ammonia yield were significantly improved.
Smart Images

Figure CN119461329A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new materials and electrocatalysis, and in particular to a preparation method and application of carbon-coated cobalt phosphide and carbon-coated cobalt phosphide loaded with carbon nitride. Background Art
[0002] Ammonia is an important chemical raw material in modern industry. At present, the process of synthesizing ammonia mainly relies on the Haber-Bosch process, which requires high temperature and high pressure reaction conditions and consumes a large amount of fossil energy, bringing about a huge energy and environmental crisis. x RR) is considered to be a promising NH 3 Production pathway, because NO 3 - / NO 2 - It has a lower N=O bond dissociation energy, high solubility, and a relatively more positive potential for reduction reaction, which can inhibit the competitive hydrogen evolution reaction (HER) to a certain extent. x RR is a complex multi-electron process and involves multiple intermediate reactions, which poses a challenge to the synthesis of NH 3 Therefore, it is urgent to develop NO with high activity, high selectivity and durability. x RR Catalyst.
[0003] Transition metal phosphides (TMP) have the advantages of simple synthesis and low price. They also have the advantages of rich crystal structure composition, more changes in the coordination ratio between transition metals and P atoms, and easy to change and regulate the surface chemical state. Literature confirms that TMP is an effective catalytic NO x For RR reduced catalysts, using carbon materials to stably support and coat TMP can effectively improve the stability and efficiency of the catalyst.
[0004] However, simple and economical methods for synthesizing carbon-coated cobalt phosphide nanomaterials are still scarce. There are currently reported cases of synthesizing carbon-coated cobalt phosphide, and most of the synthesis methods are high-temperature pyrolysis of metal organic frameworks (MOFs) materials or high-temperature decomposition of biomass materials. The preparation of MOFs precursors is expensive and the synthesis steps are complicated. Biomass carbon synthesis often requires complex pretreatment and the carbonization reaction temperature needs to be above 700°C. For various reasons, the synthesis of carbon-coated cobalt phosphide becomes difficult. x There are few literatures on RR reaction, and the synthesized carbon-coated cobalt phosphide is applied to NO x During the RR reaction, the disadvantages include violent hydrogen evolution reaction, low selectivity of ammonia synthesis, and poor catalytic stability.
[0005] Therefore, it is of great theoretical and practical significance to develop a simple, efficient and controllable synthesis method to obtain high-performance carbon-coated cobalt phosphide catalyst for the electrocatalytic reaction of nitrite / nitrate to synthesize ammonia. Summary of the invention
[0006] In order to solve the problems existing in the above-mentioned prior art, the present invention provides a preparation method of carbon-coated cobalt phosphide and carbon-coated cobalt phosphide loaded with carbon nitride and its application, wherein a cobalt Schiff base complex is used to prepare carbon-coated cobalt phosphide, and the preparation cost of small molecule cobalt Schiff base is low, the process is simple and the yield is high, and the thermal cracking temperature is low, which greatly reduces the cost and time of synthesizing carbon-coated cobalt phosphide; and further by adding carbon nitride (C 3 N 4 ) regulates the particle size of carbon-coated cobalt phosphide. The introduction of carbon nitride further stabilizes and supports carbon-coated cobalt phosphide and provides electronic regulation of the catalyst, thereby increasing the binding energy of the Co-P bond and being more conducive to the reaction of the substrate (NO 2 - ) adsorption and product (NH 4 + ) desorption, so that the reaction proceeds faster. The carbon-coated cobalt phosphide and carbon-coated cobalt phosphide loaded carbon nitride prepared by the present invention are used as catalysts in the electrocatalytic nitrite reduction ammonia synthesis process under normal temperature and pressure conditions, and have significant catalytic effects and excellent cyclic catalytic stability.
[0007] The method for preparing carbon-coated cobalt phosphide by synthesizing cobalt Schiff base provided by the present invention comprises the following specific steps:
[0008] (1) o-phenylenediamine and salicylaldehyde are added to a volumetric flask in a certain molar ratio, an appropriate amount of ethanol is added to dissolve, the mixture is heated to reflux, and after cooling, an orange solid is obtained by suction filtration, and the solid is placed in a vacuum drying oven for drying to obtain a Schiff base ligand;
[0009] The molar ratio of o-phenylenediamine to salicylaldehyde is 1:2, the amount of ethanol is 100-150 mL, the heating temperature is 60-70° C., the reflux time is 1 h, and the drying temperature is 60° C.
[0010] (2) adding the Schiff base ligand and cobalt chloride hexahydrate into a volumetric flask in a certain molar ratio, adding an appropriate amount of ethanol, heating and reflux under a nitrogen atmosphere, and then rotary evaporating to obtain a dark green solid, i.e., the cobalt Schiff base complex;
[0011] The molar ratio of the Schiff base ligand to cobalt chloride hexahydrate is 1:1, the amount of ethanol used is 100-150 mL, the heating temperature is 50-60° C., and the reflux time is 0.5-1 h.
[0012] (3) Weigh a certain mass of cobalt Schiff base complex and put it into one end of a porcelain boat, and put a certain mass of sodium hypophosphite into the other end of the porcelain boat, put the porcelain boat into a tube furnace, and put the end containing sodium hypophosphite into the air inlet of the tube furnace, and heat and calcine under argon atmosphere, wash the obtained black solid with water and anhydrous ethanol and centrifuge it three times, and then put the solid into an oven to dry, and the solid finally obtained is carbon-coated cobalt phosphide (CoP@C);
[0013] The mass ratio of the cobalt Schiff base complex to the sodium hypophosphite is 1:10, the heating rate of the tubular furnace is 5°C / min, the heating temperature is 350°C, and the calcination is performed for 2h after reaching 350°C. The drying temperature is 60°C.
[0014] In order to obtain a structure-regulated carbon-coated cobalt phosphide nanomaterial, the present invention further adds a carbon nitride flake material to the above system to regulate the morphology of cobalt phosphide. On the basis of the above steps (1) and (2), the preparation steps of carbon-coated cobalt phosphide loaded with carbon nitride are as follows:
[0015] (3) dissolving dicyandiamide (DCDA) and sodium chloride (NaCl) in deionized water at a certain molar ratio under continuous magnetic stirring, freezing the resulting solution in a refrigerator, and then freeze-drying and dehydrating the solution to obtain a fluffy white powder, which is then heated and calcined under an argon atmosphere, and the obtained yellow or brown powder is washed with water several times to fully remove NaCl, and then freeze-dried to obtain carbon nitride;
[0016] In step (3), the molar ratio of dicyandiamide to sodium chloride is 1:10, the freezing temperature in the refrigerator is -20°C, the freezing time is 12h, the freeze-drying temperature is -40°C, the freeze-drying time is 24h, the heating rate is 2°C / min, the heating temperature is 520°C, and the calcination is performed for 4h after reaching 520°C.
[0017] (4) The cobalt Schiff base complex obtained in step (2) and carbon nitride are mixed in a certain mass ratio, and then fully ground and mixed, and placed at one end of a porcelain boat, and a certain mass of sodium hypophosphite is placed at the other end of the porcelain boat, and the porcelain boat is placed in a tubular furnace, and the end containing sodium hypophosphite is placed at the air inlet of the tubular furnace, and the temperature is increased and calcined under an argon atmosphere, and the obtained black solid is washed with water and anhydrous ethanol and centrifuged three times, and then the solid is placed in an oven for drying, and the obtained gray solid is carbon-coated cobalt phosphide loaded carbon nitride nanomaterial (CoP@C / C 3 N 4 )
[0018] The mass ratio of the cobalt Schiff base complex obtained in step (2) to carbon nitride is 1:1, and the mass ratio of the mixture of the cobalt Schiff base complex and carbon nitride to sodium hypophosphite is 1:5; the heating rate is 5°C / min, the heating temperature is 350°C, and after reaching 350°C, calcination is performed for 2h, and the drying temperature is 60°C.
[0019] In the above steps, the Schiff base in step (1) is formed by a nucleophilic addition reaction between salicylaldehyde and o-phenylenediamine, and the aldehyde or ketone compound containing a carbonyl group undergoes a nucleophilic addition reaction with a primary amine compound. The nucleophilic reagent is an amine compound, and the nitrogen atom with a lone electron pair in the compound structure can attack the carbon atom with a positive charge on the carbonyl group to complete the nucleophilic addition reaction, forming an intermediate α-hydroxyamine compound, which is then further dehydrated to form a Schiff base ligand. In step (2), the Schiff base ligand has N 2 O 2 The coordination group can coordinate with a wide range of metals, and in this step, it can coordinate with cobalt. In step (3), sodium hypophosphite decomposes at high temperature to produce PH 3 Gas, PH is adjusted by purging with argon 3 It is sent to one end of the cobalt Schiff base complex, where the Schiff base complex will undergo a thermal cracking reaction at high temperature and will be phosphated at the same time. In this way, it can be synthesized through a one-step thermal cracking and phosphating method, which is simple and has lower cost.
[0020] In step (3) of preparing carbon-coated cobalt phosphide loaded with carbon nitride, NaCl is used as a template to synthesize carbon nitride into flakes, and dicyandiamide undergoes a thermal condensation reaction at 520° C. to generate carbon nitride. In step (4), carbon nitride is introduced into the carbon-coated cobalt phosphide, further increasing the stability of the catalyst.
[0021] The particle size of the carbon-coated cobalt phosphide and carbon-coated cobalt phosphide-loaded carbon nitride materials can be observed to have reached nanometer level through TEM.
[0022] The carbon-coated cobalt phosphide nanomaterial prepared by the above method can be used as a catalyst for electrocatalytic nitrite synthesis of ammonia. The specific operation steps are as follows:
[0023] The prepared carbon-coated cobalt phosphide and carbon-coated cobalt phosphide loaded carbon nitride were placed in centrifuge tubes respectively, anhydrous ethanol was added to the tubes, and then 5% perfluoronaphthol sulfonate membrane solution was added dropwise, and ultrasonic treatment was performed for 1 hour to fully disperse it in the solution. The solution was added dropwise onto a glassy carbon electrode, and the following electrochemical tests were performed after natural evaporation.
[0024] The polarization curves (LSV) were obtained in 1M NaOH solution and 1M NaOH+0.1M NaNO 2In the solution, the working electrode was a glassy carbon electrode (0.6 cm in diameter) loaded with a catalyst, Ag / AgCl was used as a reference electrode, and a carbon rod was used as a counter electrode for testing. The test voltage range was -0.6 V vs. RHE—0.2 V vs. RHE, and the test scan rate was 5 mV / s.
[0025] In 1M NaOH + 0.1M NaNO 2 In the solution, electrolysis (BE) tests were carried out at -0.3 V vs. RHE, -0.4 V vs. RHE, -0.5 V vs. RHE, -0.6 V vs. RHE and -0.7 V vs. RHE for 1 h.
[0026] After the electrolysis (BE) test and the electrocatalytic reaction are completed, the electrolyte is taken into a colorimetric tube, diluted with a 1 mol / L NaOH solution, and potassium sodium tartrate solution and potassium mercuric iodide solution (Nessler reagent spectrophotometry) are added dropwise in sequence. After standing for 15 minutes, the absorbance at a wavelength of 420 nm is detected using a UV-visible absorption spectrometer. According to the national standard Nessler reagent spectrophotometry, a standard ammonia solution is used as a standard curve, and the ammonia yield and Faraday efficiency of the electrocatalytic system are obtained according to the sample test results.
[0027] The calculation shows that the Faraday efficiency of the electrocatalytic synthesis of ammonia by carbon-coated cobalt phosphide is 81.9%, and the ammonia yield is 152 μmol·h -1 cm -2 The electrocatalytic synthesis of ammonia by carbon-coated cobalt phosphide supported carbon nitride has a Faraday efficiency of 91.17% and an ammonia yield of 394.19 μmol·h -1 cm -2 .
[0028] BE test was carried out at the optimum voltage of the catalyst -0.5V vs. RHE to test its cycle stability. After 12h of cycling, the Faraday efficiency of carbon-coated cobalt phosphide was 70.62%, and the Faraday efficiency of carbon-coated cobalt phosphide loaded with carbon nitride was 85.49%. After the introduction of carbon nitride, the catalytic performance was further improved.
[0029] In summary, the present invention provides a method for preparing carbon-coated cobalt phosphide nanomaterials, especially carbon-coated cobalt phosphide and carbon-coated cobalt phosphide-loaded carbon nitride, which is prepared and synthesized by a one-step thermal cracking phosphating method of a cobalt Schiff base complex, overcoming the shortcomings of the traditional carbon-coated cobalt phosphide synthesis process, such as complex and high cost, and further adding carbon nitride as a carrier to support and control the morphology of the carbon-coated cobalt phosphide, providing the role of electronic regulation of the catalyst. The carbon-coated cobalt phosphide-loaded carbon nitride prepared by the present invention is used in the electrocatalytic nitrite reduction synthesis of ammonia process. Due to the introduction of carbon nitride, the binding energy of the Co-P bond is increased, which is more conducive to the reaction of the substrate (NO at the active site). 2- ) adsorption and product (NH 4 + ) desorption, making the reaction proceed faster in the forward direction, with higher electrocatalytic synthesis efficiency and good catalytic stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The reaction equation for preparing the cobalt Schiff base complex of the present invention;
[0031] Figure 2 The Schiff base ligand prepared in Example 1 1 H NMR spectra;
[0032] Figure 3 is the fitting diagram of HRMS of the cobalt Schiff base prepared in Example 1;
[0033] Figure 4 This is the XRD pattern of the carbon-coated cobalt phosphide prepared in Example 1;
[0034] Figure 5 This is a SEM image of the carbon-coated cobalt phosphide prepared in Example 1;
[0035] Figure 6 TEM, HRTEM, and mapping images of the carbon-coated cobalt phosphide prepared in Example 1; a and b are TEM images, c is an HRTEM image, and d is a mapping image;
[0036] Figure 7 The XPS Co 2p spectrum of the carbon-coated cobalt phosphide prepared in Example 1;
[0037] Figure 8 This is the C1s spectrum of the XPS of the carbon-coated cobalt phosphide prepared in Example 1;
[0038] Fig. 9 This is the XRD pattern of carbon-coated cobalt phosphide supported carbon nitride prepared in Example 2;
[0039] Fig.10 This is a SEM image of the carbon nitride prepared in Example 2;
[0040] Fig.11 This is the C1s spectrum of the XPS of the carbon nitride prepared in Example 2;
[0041] Fig.12 This is a SEM image of carbon-coated cobalt phosphide loaded with carbon nitride prepared in Example 2;
[0042] Fig.13TEM, HRTEM, and mapping images of carbon-coated cobalt phosphide loaded with carbon nitride prepared in Example 2; a and b are TEM images, c is an HRTEM image, and d is a mapping image;
[0043] Fig.14 The XPS Co 2p spectrum of carbon-coated cobalt phosphide supported carbon nitride prepared in Example 2;
[0044] Fig.15 This is the C1s spectrum of the XPS of the carbon-coated cobalt phosphide supported carbon nitride prepared in Example 2;
[0045] Fig.16 This is the LSV diagram of the electrocatalytic synthesis of ammonia from nitrite by the carbon-coated cobalt phosphide prepared in Example 1;
[0046] Fig.17 The graph is a graph showing the Faraday efficiency and ammonia yield of the carbon-coated cobalt phosphide prepared in Example 1 for electrocatalytic synthesis of ammonia at different voltages;
[0047] Fig.18 This is a test diagram of the cyclic stability of the carbon-coated cobalt phosphide prepared in Example 1;
[0048] Fig.19 This is the LSV diagram of the electrocatalytic synthesis of ammonia from nitrite by carbon-coated cobalt phosphide supported carbon nitride prepared in Example 2;
[0049] Fig. 20 The Faraday efficiency and ammonia yield curve of the carbon-coated cobalt phosphide supported carbon nitride electrocatalytically synthesizing ammonia at different voltages prepared in Example 2;
[0050] Fig.21 This is a cyclic stability test chart of the carbon-coated cobalt phosphide loaded with carbon nitride prepared in Example 2. DETAILED DESCRIPTION
[0051] The present invention will be further described below in conjunction with specific embodiments, so that those skilled in the art can understand the present invention more comprehensively, but the present invention is not limited in any way. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0052] Example 1
[0053] The preparation method of carbon-coated cobalt phosphide (CoP@C) material, the reaction equation is as follows Figure 1 As shown, the specific steps include:
[0054] (1) Preparation of Schiff base ligands
[0055] 0.01 mol (1.08 g) of o-phenylenediamine and 0.02 mol (2.44 g) of salicylaldehyde were added to a 250 mL volumetric flask, and 100 mL of ethanol was added. The mixture was heated under reflux at 60°C-70°C for 1 h. After cooling, an orange solid was filtered out to obtain the solid. The solid was dried in a vacuum drying oven at 60°C to obtain a Schiff base ligand with a yield of 98%.
[0056] (2) Preparation of cobalt Schiff base complexes
[0057] 0.001 mol (0.316 g) of Schiff base and 0.001 mol (0.238 g) of cobalt chloride hexahydrate were added into a 250 mL volumetric flask, and 100 mL of ethanol was added. The mixture was heated to reflux at 50-60° C. for 30 min under a nitrogen atmosphere. After cooling, the mixture was evaporated to obtain a dark green solid, i.e., the cobalt Schiff base complex.
[0058] (3) Preparation of carbon-coated cobalt phosphide (CoP@C)
[0059] Weigh 0.1 g of the cobalt complex and put it into one end of the porcelain boat, and put 1 g of sodium hypophosphite into the other end of the porcelain boat. The porcelain boat is placed in a tubular furnace, and the end containing the sodium hypophosphite is placed at the air inlet of the tubular furnace. The temperature is increased to 350°C at a heating rate of 5°C / min under an argon atmosphere, and then calcined at this temperature for 2 hours. The obtained black solid is washed with water and anhydrous ethanol and centrifuged three times, and then the solid is placed in a 60°C oven for drying to obtain carbon-coated cobalt phosphide (CoP@C).
[0060] The test characterization data of the Schiff base ligand, cobalt Schiff base complex and carbon-coated cobalt phosphide material prepared above are as follows:
[0061] Figure 2 The peak at 8.63 ppm is the resonance of the proton on the -CH=N of the Schiff base. The existence of this peak also confirms the stability of the Schiff base obtained by the synthesis method of the present invention. Figure 2 The other peaks were integrated with the peak area of 8.63 ppm as 1, and δ = 7.35 (m, 6H, Ar), 7.25 (m, 2H, Ar), 7.05 (d, 2H, Ar), 6.9 (t, 2H, Ar), confirming the successful synthesis of the Schiff base.
[0062] Figure 3 This is the high-resolution mass spectrum fitting diagram of the cobalt Schiff base complex. From the figure, we can see that the highest peak of m / z is 408, and it can be inferred that the molecular formula of the cobalt Schiff base is [Co(C 20 H 14 N 2 O 2 )]Cl, demonstrating the successful preparation of cobalt Schiff base.
[0063] Figure 4 This is the XRD pattern of carbon-coated cobalt phosphide material. The 2θ values in the spectrum are 31.6°, 35.3°, 36.3°, 46.2°, 48.1°, 52.3°, 56°, and 56.8°, which correspond to the (011), (200), (111), (112), (211), (103), (020), and (301) crystal planes of CoP (PDF#89-2747), respectively. The diffraction peaks of the XRD pattern of this material match those of CoP (PDF#89-2747), and the bulge at about 15° is the characteristic peak of carbon in carbon-coated cobalt phosphide material.
[0064] Figure 5 This is a scanning electron microscope (SEM) image of the carbon-coated cobalt phosphide material. From the image, it can be seen that the carbon-coated cobalt phosphide material is a block material of uneven size.
[0065] Figure 6 TEM, HRTEM, and mapping images of carbon-coated cobalt phosphide, where a and b are TEM images, c is an HRTEM image, and d is a mapping image. It can be seen from Figures a and b that the cobalt phosphide is in the form of clustered nanoparticles on the inside and the carbon layers on the outside are tightly connected. The lattice of CoP on the (111) crystal plane is observed in Figure c, and the uniform distribution of Co, P, C, and N is observed in Figure d, proving the successful synthesis of carbon-coated cobalt phosphide.
[0066] Figure 7 This is the X-ray photoelectron spectrum (XPS) of carbon-coated cobalt phosphide material. This is the Co 2p spectrum, in which the two deconvolution peaks at 780.45 and 796.35 correspond to Co-P bonds, proving the successful preparation of cobalt phosphide.
[0067] Figure 8 This is the X-ray photoelectron spectrum (XPS) of carbon-coated cobalt phosphide material, which is the C1s spectrum. There are CC (284.8eV), CN (286.1eV), and CO (289.2eV), among which the CO bond comes from surface oxidation, proving the presence of carbon.
[0068] Example 2
[0069] Carbon-coated cobalt phosphide loaded with carbon nitride (CoP@C / C 3 N 4 ) material preparation method, comprising the following steps:
[0070] (1) Preparation of Schiff base ligands
[0071] Same as step (1) of Example 1.
[0072] (2) Preparation of cobalt Schiff base complexes
[0073] Same as step (2) in Example 1.
[0074] (3) Preparation of carbon nitride
[0075] 2.52g of dicyandiamide (DCDA) and 17.53g of sodium chloride (NaCl) were dissolved in 100mL of deionized water at a molar ratio of 1:10 under continuous magnetic stirring for 12h, and the resulting solution was placed in a refrigerator for freezing at -20°C for 12h, and then freeze-dried at -40°C for 24h to obtain fluffy white powder. The temperature was raised to 520°C at a rate of 2°C / min under an argon atmosphere, and then calcined at this temperature for 4h. The obtained yellow or brown powder was washed with water several times to fully remove NaCl, and then freeze-dried to obtain carbon nitride.
[0076] (4) Preparation of carbon-coated cobalt phosphide loaded carbon nitride
[0077] 0.1 g of cobalt Schiff base complex and 0.2 g of carbon nitride were fully ground and placed at one end of a porcelain boat, and 1 g of sodium hypophosphite was placed at the other end of the porcelain boat. The porcelain boat was placed in a tube furnace, and the end containing sodium hypophosphite was placed at the air inlet of the tube furnace. The temperature was raised to 350 ° C at a heating rate of 5 ° C / min under an argon atmosphere, and then calcined at this temperature for 2 h. The obtained black solid was washed with water and anhydrous ethanol and centrifuged three times, and then the solid was placed in a 60 ° C oven to dry to obtain carbon-coated cobalt phosphide supported carbon nitride (CoP@C / C 3 N 4 ).
[0078] The carbon nitride and carbon-coated cobalt phosphide materials prepared in Example 2 were subjected to the following tests and characterizations:
[0079] Fig. 9 The XRD pattern of carbon-coated cobalt phosphide loaded carbon nitride, where 27.8° is C 3 N 4 The other characteristic peaks at 31.6°, 36.3°, and 48.1° are in good agreement with the characteristic peaks of CoP (PDF#89-2747).
[0080] Fig.10 This is the SEM image of carbon nitride. It can be seen from the image that carbon nitride is a flaky material, which is conducive to supporting the catalyst.
[0081] Fig.11 The C1s spectrum of XPS of carbon nitride shows the presence of CC (284.8 eV) and C=NC (288.2 eV), proving the successful synthesis of carbon nitride.
[0082] Fig.12This is the SEM image of carbon-coated cobalt phosphide loaded with carbon nitride material. It can be seen from the figure that the size of the material is further reduced after loading with carbon nitride, and the particle size tends to be uniform, indicating that carbon nitride has the function of regulating the size of the material.
[0083] Fig.13 TEM, HRTEM and mapping images of carbon-coated cobalt phosphide loaded with carbon nitride, where a and b are TEM images, c is an HRTEM image, and d is a mapping image. It can be seen from Figures a and b that the darker part is where the carbon-coated cobalt phosphide exists. From Figure c, the lattice stripes of cobalt phosphide on the (111) crystal plane are observed. It can also be seen from Figure d that there is a higher distribution of carbon elements near cobalt phosphide, which proves the successful synthesis of cobalt phosphide and the successful introduction of carbon nitride. At the same time, it can be seen that the size of the carbon-coated cobalt phosphide material is significantly reduced after loading carbon nitride.
[0084] Fig.14 This is the XPS Co 2p spectrum of carbon-coated cobalt phosphide material, where the two deconvolution peaks at 780.75 eV and 799.9 eV correspond to Co-P bonds, proving the successful preparation of carbon-coated cobalt phosphide supported carbon nitride.
[0085] Fig.15 The C1s spectrum of XPS of carbon-coated cobalt phosphide material shows CC (284.6 eV), CN (286.1 eV), and C=NC (288.4 eV), which proves the successful loading of carbon nitride and the successful synthesis of carbon-coated cobalt phosphide.
[0086] Application Example 1: Electrocatalytic synthesis of ammonia from nitrite using carbon-coated cobalt phosphide
[0087] The carbon-encapsulated cobalt phosphide material prepared in Example 1 was subjected to an electrocatalytic ammonia synthesis performance test. The electrochemical performance test adopted a three-electrode system of a CHI 604E electrochemical workstation standard. The specific process of testing the electrocatalytic ammonia synthesis performance of the carbon-encapsulated cobalt phosphide material is as follows:
[0088] Take 4 mg of the carbon-coated cobalt phosphide sample prepared in Example 1 and put it in a 2 mL centrifuge tube. Take 500 μL of anhydrous ethanol and add it to the tube. Then add 50 μL of 5% perfluoronaphthol sulfonate membrane solution. Ultrasonicate for 1 hour to fully disperse it in the solution. Take 10 μL of the solution and add it to the glassy carbon electrode. After natural evaporation, perform the following electrochemical test.
[0089] The polarization curves (LSV) were obtained in 1M NaOH solution and 1M NaOH+0.1M NaNO 2In the solution, the working electrode was a glassy carbon electrode (0.6 cm in diameter) loaded with a catalyst, Ag / AgCl was used as a reference electrode, and a carbon rod was used as a counter electrode for testing. The test voltage range was -0.6 V vs. RHE—0.2 V vs. RHE, and the test scan rate was 5 mV / s.
[0090] Fig.16 Carbon-coated cobalt phosphide in 1M NaOH solution and 1M NaOH + 0.1M NaNO 2 The LSV curve of the solution shows that when 0.1M NaNO is added 2 The initial voltage was advanced and the current density increased, indicating that carbon-coated cobalt phosphide has good electrocatalytic performance for nitrite.
[0091] In 1M NaOH + 0.1M NaNO 2 In the solution, electrolysis (BE) tests were carried out at -0.3 V vs. RHE, -0.4 V vs. RHE, -0.5 V vs. RHE, -0.6 V vs. RHE and -0.7 V vs. RHE for 1 h.
[0092] After the electrolysis (BE) test and the electrocatalytic reaction are completed, 0.5 mL of electrolyte is taken into a 25 mL colorimetric tube, diluted to 25 mL with 1 mol / L NaOH, and potassium sodium tartrate solution and potassium mercuric iodide solution (Nessler reagent spectrophotometry) are added dropwise in sequence. After standing for 15 minutes, the absorbance at a wavelength of 420 nm is detected by a UV-visible absorption spectrometer. According to the national standard Nessler reagent spectrophotometry, a standard ammonia solution is used as a standard curve, and the ammonia yield and Faraday efficiency of the electrocatalytic system are obtained according to the sample test results.
[0093] Ammonia yield v(NH 3 )=(C(NH 3 )×V) / (t×A), where C(NH 3 ) is the measured concentration of ammonia, μmol / L; V is the volume of electrolyte in the cathode compartment, L; F is the Faraday constant, 96500C mol -1 .
[0094] Faraday efficiency FE(NO 2 - )=(6×C(NH 3 )×V×F) / Q, where t is the electrolysis time, h; A is the geometric area of the working electrode. In this experiment, the geometric area of the iron foam used was 1 cm 2 .
[0095] Fig.17The electrocatalytic ammonia yield and Faraday efficiency of carbon-coated cobalt phosphide were calculated by ultraviolet spectrophotometry after electrolysis test. It can be seen from the figure that the Faraday efficiency of carbon-coated cobalt phosphide material for electrolysis reaches the highest at a voltage of -0.5Vvs.RHE, which is 81.9%, and the ammonia yield is 152μmol·h -1 cm -2 .
[0096] In 1M NaOH + 0.1M NaNO 2 In the solution, a 12h electrolysis (BE) test was carried out at the optimal voltage of -0.5V vs.RHE to characterize the catalytic stability of carbon-coated cobalt phosphide.
[0097] Similarly, after the electrolysis (BE) test and the electrocatalytic reaction are completed, the electrolyte is tested using the above method to obtain the ammonia yield and Faraday efficiency of the electrocatalytic system.
[0098] Fig.18 This is a test diagram of the cyclic stability of carbon-coated cobalt phosphide. It can be seen from the figure that after a 12-h electrolysis test at the optimum voltage of -0.5 V vs. RHE, the Faraday efficiency of the electrocatalytic synthesis of ammonia is 70.6%, indicating that the carbon-coated cobalt phosphide prepared in Example 1 has good catalytic stability.
[0099] Application Example 2: Electrocatalytic synthesis of ammonia from nitrite by carbon-coated cobalt phosphide supported carbon nitride
[0100] The carbon-coated cobalt phosphide-supported carbon nitride material prepared in Example 2 was subjected to an electrocatalytic ammonia synthesis performance test. The electrochemical performance test adopted a three-electrode system of a CHI 604E electrochemical workstation standard. The specific process of testing the electrocatalytic ammonia synthesis performance of the carbon-coated cobalt phosphide-supported carbon nitride is as follows:
[0101] Take 4 mg of the carbon-coated cobalt phosphide loaded carbon nitride sample prepared in Example 2 and put it in a 2 mL centrifuge tube. Take 500 μL of anhydrous ethanol and add it to the tube. Then add 50 μL of 5% perfluoronaphthol sulfonate membrane solution. Ultrasonicate for 1 hour to make it fully dispersed in the solution. Take 10 μL of the solution and add it dropwise to the glassy carbon electrode. After natural evaporation, perform the following electrochemical test.
[0102] The polarization curves (LSV) were obtained in 1M NaOH solution and 1M NaOH+0.1M NaNO 2 In the solution, the working electrode was a glassy carbon electrode (0.6 cm in diameter) loaded with a catalyst, Ag / AgCl was used as a reference electrode, and a carbon rod was used as a counter electrode for testing. The test voltage range was -0.6 V vs. RHE—0.2 V vs. RHE, and the test scan rate was 5 mV / s.
[0103] Fig.19Carbon nitride was loaded on carbon-coated cobalt phosphide in 1M NaOH solution and 1M NaOH + 0.1M NaNO 2 The LSV curve of the solution shows that when 0.1M NaNO is added 2 The starting voltage is advanced, the current density is increased, and compared with carbon-coated cobalt phosphide, it has an earlier starting voltage and a higher current density, indicating that carbon-coated cobalt phosphide loading has better electrocatalytic nitrite performance.
[0104] In 1M NaOH + 0.1M NaNO 2 In the solution, electrolysis (BE) tests were carried out at -0.3 V vs. RHE, -0.4 V vs. RHE, -0.5 V vs. RHE, -0.6 V vs. RHE and -0.7 V vs. RHE for 1 h.
[0105] After the electrolysis (BE) test and the electrocatalytic reaction are completed, 0.5 mL of electrolyte is taken into a 25 mL colorimetric tube, diluted to 25 mL with 1 mol / L NaOH, and potassium sodium tartrate solution and potassium mercuric iodide solution (Nessler reagent spectrophotometry) are added dropwise in sequence. After standing for 15 minutes, the absorbance at a wavelength of 420 nm is detected using a UV-visible absorption spectrometer. According to the national standard Nessler reagent spectrophotometry, a standard ammonia solution is used as a standard curve, and the ammonia yield and Faraday efficiency of the electrocatalytic system are obtained according to the sample test results.
[0106] Fig. 20 The electrocatalytic ammonia yield and Faraday efficiency of carbon-coated cobalt phosphide loaded carbon nitride were calculated by ultraviolet spectrophotometry after electrolysis test. The Faraday efficiency of the electrolysis material obtained in the figure reached the highest at a voltage of -0.5V vs. RHE, which was 91.17%, and the ammonia yield was 394.19μmol·h -1 cm -2 .
[0107] In 1M NaOH + 0.1M NaNO 2 In the solution, a 12h electrolysis (BE) test was carried out at the optimal voltage of -0.5V vs.RHE to characterize the catalytic stability of carbon-coated cobalt phosphide supported carbon nitride.
[0108] Similarly, after the electrolysis (BE) test and the electrocatalytic reaction are completed, the electrolyte is tested using the above method to obtain the ammonia yield and Faraday efficiency of the electrocatalytic system.
[0109] Fig.21This is a cyclic stability test diagram of carbon-coated cobalt phosphide loaded with carbon nitride. It can be seen from the figure that after a 12-h electrolysis test at the optimal voltage of -0.5V vs. RHE, the Faraday efficiency of electrocatalytic synthesis of ammonia is 85.5%, indicating that after the introduction of carbon nitride, the stability of the catalyst is further improved.
[0110] In summary, the carbon-coated cobalt phosphide and the carbon-coated cobalt phosphide-loaded carbon nitride material obtained by this method can be used as catalysts to electrocatalyze nitrite reduction to synthesize ammonia under normal temperature and pressure conditions, and have significant catalytic effects and excellent cyclic catalytic stability.
[0111] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any equivalent substitutions, modifications, etc. made by technicians in this field without any creative work within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing carbon-coated cobalt phosphide, characterized in that: The specific steps are as follows: (1) o-phenylenediamine and salicylaldehyde are added to a volumetric flask in a certain molar ratio, an appropriate amount of ethanol is added to dissolve, the mixture is heated to reflux, and after cooling, an orange solid is obtained by suction filtration, and the solid is placed in a vacuum drying oven for drying to obtain a Schiff base ligand; (2) adding the Schiff base ligand and cobalt chloride hexahydrate into a volumetric flask in a certain molar ratio, adding an appropriate amount of ethanol, heating and reflux under a nitrogen atmosphere, and then rotary evaporating to obtain a dark green solid, i.e., the cobalt Schiff base complex; (3) Weigh a certain mass of cobalt Schiff base complex and put it into one end of a porcelain boat, and put a certain mass of sodium hypophosphite into the other end of the porcelain boat. The porcelain boat is placed in a tubular furnace, and the end containing sodium hypophosphite is placed at the air inlet of the tubular furnace. The temperature is increased and calcined in an argon atmosphere. The obtained black solid is washed with water and anhydrous ethanol and centrifuged three times. Then the solid is placed in an oven for drying. The solid finally obtained is carbon-coated cobalt phosphide.
2. The method for preparing carbon-coated cobalt phosphide according to claim 1, characterized in that: In step (1), the molar ratio of o-phenylenediamine to salicylaldehyde is 1:2, the heating temperature is 60-70°C, the reflux time is 1h, and the drying temperature is 60°C.
3. The method for preparing carbon-coated cobalt phosphide according to claim 1, characterized in that: In step (2), the molar ratio of the Schiff base ligand to cobalt chloride hexahydrate is 1:1, the heating temperature is 50-60° C., and the reflux time is 0.5-1 h.
4. The method for preparing carbon-coated cobalt phosphide according to claim 1, characterized in that: In step (3), the mass ratio of the cobalt Schiff base complex to the sodium hypophosphite is 1:10, the heating rate is 5°C / min, the heating temperature is 350°C, and after reaching 350°C, calcination is performed for 2h, and the drying temperature is 60°C.
5. A method for preparing carbon-coated cobalt phosphide loaded carbon nitride, characterized in that: The specific steps are as follows: (1) o-phenylenediamine and salicylaldehyde are added to a volumetric flask in a certain molar ratio, an appropriate amount of ethanol is added to dissolve, the mixture is heated to reflux, and after cooling, an orange solid is obtained by suction filtration, and the solid is placed in a vacuum drying oven for drying to obtain a Schiff base ligand; (2) adding the Schiff base ligand and cobalt chloride hexahydrate into a volumetric flask in a certain molar ratio, adding an appropriate amount of ethanol, heating and reflux under a nitrogen atmosphere, and then rotary evaporating to obtain a dark green solid, i.e., the cobalt Schiff base complex; (3) dissolving dicyandiamide and sodium chloride in deionized water at a certain molar ratio under continuous magnetic stirring, freezing the resulting solution in a refrigerator, and then freeze-drying and dehydrating the solution to obtain a fluffy white powder, which is then heated and calcined under an argon atmosphere, and the obtained yellow or brown powder is washed with water several times to fully remove NaCl, and then freeze-dried to obtain carbon nitride; (4) Cobalt Schiff base and carbon nitride are mixed in a certain mass ratio and then fully ground and placed at one end of a porcelain boat. A certain mass of sodium hypophosphite is placed at the other end of the porcelain boat. The porcelain boat is placed in a tubular furnace. The end containing sodium hypophosphite is placed at the air inlet of the tubular furnace. The temperature is increased and calcined under an argon atmosphere. The obtained black solid is washed with water and anhydrous ethanol and centrifuged three times. The solid is then placed in an oven for drying. The obtained gray solid is the carbon-coated cobalt phosphide-loaded carbon nitride nanomaterial.
6. The method for preparing carbon-coated cobalt phosphide loaded carbon nitride according to claim 5, characterized in that: In step (1), the molar ratio of o-phenylenediamine to salicylaldehyde is 1:2, the heating temperature is 60-70° C., and the reflux time is 1 h; in step (2), the molar ratio of Schiff base ligand to cobalt chloride hexahydrate is 1:1, the heating temperature is 50-60° C., and the reflux time is 0.5-1 h.
7. The method for preparing carbon-coated cobalt phosphide loaded carbon nitride according to claim 5, characterized in that: In step (3), the molar ratio of dicyandiamide to sodium chloride is 1:10, the freezing temperature in the refrigerator is -20°C, the freezing time is 12h, the freeze-drying temperature is -40°C, the freeze-drying time is 24h, the heating rate is 2°C / min, the heating temperature is 520°C, and the calcination is performed for 4h after reaching 520°C.
8. The method for preparing carbon-coated cobalt phosphide loaded carbon nitride according to claim 5, characterized in that: In step (4), the mass ratio of cobalt Schiff base to carbon nitride is 1:1, the mass ratio of the mixture of cobalt Schiff base complex and carbon nitride to sodium hypophosphite is 1:5, the heating rate is 5°C / min, the heating temperature is 350°C, and after reaching 350°C, calcination is performed for 2h, and the drying temperature is 60°C.
9. Use of the carbon-coated cobalt phosphide according to claim 1 as a catalyst in electrocatalytic nitrite synthesis of ammonia.
10. Use of the carbon-coated cobalt phosphide loaded carbon nitride as claimed in claim 5 as a catalyst in electrocatalytic nitrite synthesis of ammonia.